Comparison of Surgical Outcomes After Open- and Double-Door Laminoplasties for Patients with Cervical Ossification of the Posterior Longitudinal Ligament: A Prospective Multicenter Study. Issue 23 (1st December 2021) - Nagoshi, Narihito; Yoshii, Toshitaka; Egawa, Satoru; Sakai, Kenichiro; Kusano, Kazuo; Nakagawa, Yukihiro; Hirai, Takashi; Wada, Kanichiro; Katsumi, Keiichi; Fujii, Kengo; Kimura, Atsushi; Furuya, Takeo; et al.
Abstract : Study Design: A prospective multicenter study. Objective: To evaluate and compare the surgical outcomes after open-door (OD) and double-door (DD) laminoplasties in subjects with cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: Although previous studies compared clinical results after OD and DD laminoplasties, they were performed at a single institution with a relatively small sample size targeting mixed pathologies, including cervical spondylotic myelopathy. Methods: This study was performed by the Japanese Multicenter Research Organization for Ossification of the Spinal Ligament. A total of 478 patients with myelopathy caused by cervical OPLL from 28 institutions were prospectively registered from 2014 to 2017 and followed up for 2 years. Of these, 41 and 164 patients received OD and DD laminoplasties, respectively. Demographic information, medical history, and imaging findings were collected. Clinical outcomes were assessed using the cervical Japanese Orthopaedic Association, Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire, and visual analog scale scores. Results: Age, sex, symptom duration, and comorbidities were not significantly different between the groups. Segmental ossification was the most frequent in both the groups. No significant differences in K-line type, canal occupying ratio, C2 to C7 angles, and range of motion were found. Both the procedures reduced the cervical range of motion postoperatively. A comparable frequency of perioperative complications was observed between the groups. The cervical Japanese Orthopaedic Association scores showed a similar improvement at 2 years postopera- tively. The reduction in visual analog scale score for neck pain was favorable in the OD group ( P = 0.02), while other pain assessments did not show any significant differences between the groups. The functional outcomes assessed using the Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire presented equivalent effective rates. Conclusion: The results demonstrated almost comparable surgical outcomes between OD and DD laminoplasties. Lamino- plasty is a valuable technique as a therapeutic option for cervical OPLL. Level of Evidence: 2